TO THE QUESTION OF THE DETERMINATION OF GEOMETRIC CHARACTERISTICS OF THE SECTION OF CORRUGATED BEAMS WITH TRAPEZOIDAL WEBS BASED ON THE SIMULATION RESULTS - Tatiana Dmitrieva; Khukhuudei Ulambaya (International Journal for Computational Civil and Structural Engineering, 2019)
An algorithm for calculating the geometric characteristics of steel I-beams with plate corrugated webs of arbitrary type is proposed. The algorithm is implemented using the I-beam with plate trapezoid webs as an example. The determination of reduced area and moments of inertia in the axes of the cross section of the trapezoidal profile based on the finite element modeling of the beam with shell elements in calculations for bending and axial compression in the “ANSYS 14.5” software package is described. The verification procedure has been performed for a shell finite element model using the example of an I-beam with a standard flat web. A table has been compiled of geometric characteristics of rod corrugated elements of a trapezoidal profile in order to realize their finite element calculation using a rod diagram. An example of the calculation of a flat frame with a horizontal corrugated element, made in software package “LIRA-SAPR” using a flat rod diagram is given.